Arastu : Hayat, Falsafa Aur Nazriyat - Ashfaq, Malik (Lahore Book Home, 2015)
Life and philosophy of Aristotle, a Greek philosopher and important founding figure of Western philosophy.
Include References.
Hayat, Falsafa Aur Nazriyat.
Keywords: Philosophers -- Philosophy, Ancient -- Greece -- Aristotle